STUDI PERHITUNGAN DAN IMPLEMENTASI AIRBAG PADA PELUNCURAN KAPAL TONGKANG 330 FEET BERDASARKAN STANDAR CB/T 3837-1998 - Dzulfiqar, Mohamad Alif; Pujo, Nur Fitri; Pamungkas, Nurman; Husen; Mufariz, Mufti Fathonah; Fadhilah, Nurul (Universitas Majalengka, 2024)
Ship launching is a crucial stage in shipbuilding, and the airbag launching method has become widely adopted due to its flexibility, cost efficiency, and better safety compared to conventional methods. The ship launching stage is a crucial part of the ship's transition from land to sea, representing a significant innovation in the maritime field. Among the various methods available, the use of airbags has become one of the most effective and widely applied techniques. The approach taken is a quantitative approach to ensure accurate calculations in the process of launching ships using airbags. The quantitative approach aims at calculating the right number and distance between airbags to ensure the safety and efficiency of ship launching, in accordance with the industry standard C/B T 3837-1998. CB/T 3837-1998 standard can be applied to ensure stability and safety during the launching process, as well as minimize the risk of damage to the ship and ensure the launching process runs smoothly. This research aims to calculate the number and distance between airbags used in the launching of a 330-foot barge. The main ship dimensions and airbag specifications were obtained through field interviews to support accurate calculations. The results show that 18 airbags are required, with a distance between airbags ranging from 6.66 to 11.78 meters using a crossover arrangement configuration. This calculation is based on the main dimensions of the ship and the specifications of the airbags used. T